In vivo applications of magnetic nanoparticle hyperthermia. (12th November 2013) - Hilger, Ingrid
Abstract: Hyperthermia is considered to be a promising tool for the treatment of tumours. Intensive research activities reveal a distinct impact not only on the cellular level but also on tumour physiology which favours the combination with the classical oncologic modalities radio- and chemotherapy. Different techniques have been established so far. Among them, magnetic hyperthermia exploits the intrinsic magnetic properties of iron oxide nanoparticles (magnetite and maghemite) which induce heating during the exposure to an alternating magnetic field. Beyond the advantage that heating is generated within the tumour and not from outside the body, the amounts of magnetic material and their intratumoral distribution patterns are key factors determining the therapeutic outcome. They can be influenced by the use of different application routes, which will be discussed in this paper.